Penerapan Metode Bercerita Untuk Meningkatkan Kemampuan Menyimak Pada Siswa Sekolah Dasar - M. Nurhan (Jurnal Sultra Elementary School, 2023)
Listening ability is one of the important aspects in language learning at the elementary school level. One of the effective methods to improve students' listening ability is the storytelling method. This article aims to examine the application of the storytelling method in improving elementary school students' listening ability through literature studies. The results of the study show that the storytelling method not only improves listening ability, but also fosters interest in learning, expands vocabulary, and strengthens understanding of cultural context. By combining relevant stories, interesting delivery techniques, and active interaction with students, this method can be an effective learning strategy.